THE SYSTEM OF RICE INTENSIFICATION (SRI) AS A SYSTEM OF AGRICULTURAL INNOVATION - Norman Upboff (Jurnal Ilmu Tanah dan Lingkungan, 2008)
The System of Rice Intensification (SRI). developed in Madagascar some 25 years ago. is gaining increasing credence and momentum as probably 500.000 farmers in more than 20 countries are now using its methods to raise their rice. production -- while also reducing their use of external inputs and production costs. Rather than focus on the innovation itself, this paper will introduce SRI only briefly, focusing instead on the transnational system for innovation that has emerged in response to this agronomic opportunity that can be particularly beneficial for resource-limited households. Within SRI's conceptual and practical framework. farmers have devised many innovations. These are the focus of a parallel paper written for this workshop. That paper considers how farmers have made the original SRI methodology less labor-intensive (even labor-saving). and how they have extended methods devised for irrigated rice production both to unirrigated (rainfed) areas for growing rice and to other crops beyond rice. This paper is concerned with what can be considered as a de facto 'system of innovation' that surrounds and has accelerated the spread of SRI worldwide. SRI has differed from most other agricultural innovations in the extent to which farmers have voluntarily invested their own time and resources in taking SRI to peers as an impressive example of farmer-to-farmer extension. Also. innovative alliances have formed among diverse persons and organizations to disseminate and adjust the methodology. thereby supporting the spread of this innovation even despite resistance from some established institutions.